Novel Melanocortin 2 Receptor Variant in a Chinese Infant With Familial Glucocorticoid Deficiency Type 1, Case Report and Review of Literature - Abuduxikuer, Kuerbanjiang; Li, Zhong-Die; Xie, Xin-Bao; Li, Yu-Chuan; Zhao, Jing; Wang, Jian-She (Frontiers in Endocrinology, 2019)
Familial glucocorticoid deficiency type 1 (FGD1) is an autosomal recessive disorder caused by mutations in melanocortin 2 receptor (MC2R) gene, characterized by low or undetectable serum cortisol level and high adrenocorticotropic hormone (ACTH) level. Clinical manifestations include hypoglycemia, seizure, skin hyperpigmentation, hyperbilirubinemia, cholestasis，and tall stature. Some dysmorphic features such as, prominent forehead, hypertelorism, broad nasal bridge, and small tapering fingers, have been reported. Children with FGD1 may have other isolated endocrine abnormalities. To date, no patient with FGD1 has been reported from mainland China. Here we report a Chinese patient with FGD1 having a novel MC2R gene variant, mild transverse palm crease, hypertelorism, and multiple endocrine abnormalities relating to all three zones of adrenal cortex and thyroid gland. We also reviewed cases with dysmorphic features or additional endocrine abnormalities.